Trait and state anxiety reduce the mere exposure effect - Ladd, Sandra L.; Gabrieli, John D. E. (Frontiers in Psychology, 2015)
The mere exposure effect refers to an affective preference elicited by exposure to previously unfamiliar items. Although it is a well-established finding, its mechanism remains uncertain, with some positing that it reflects affective processes and others positing that it reflects perceptual or motor fluency with repeated items. Here we examined whether individual differences in trait and state anxiety, which have been associated with the experience of emotion, influence the mere exposure effect. Participants’ trait (Study 1) and state (Study 2) anxiety were characterized with the State-Trait Anxiety Inventory. Greater trait and state anxiety correlated with greater negative affect and lesser positive affect. In both experiments, greater anxiety was associated with a reduced mere exposure effect. Measures of fluency (response times at study and test) were unrelated to the mere exposure effect. These findings support the role of affective processes in the mere exposure effect, and offer a new insight into the nature of anxiety such that anxiety is associated with a reduced experience of positive affect typically associated with familiarity.